2015
DOI: 10.1038/cti.2015.22
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte phosphatase‐associated phosphoprotein proteoforms analyzed using monoclonal antibodies

Abstract: Phosphatase CD45 regulates the activation of lymphocytes by controlling the level of receptor and signal molecule phosphorylation. However, it remains unknown which molecules mediate the phosphatase activity of CD45. A candidate for such a molecule is a small transmembrane adapter protein called lymphocyte phosphatase-associated phosphoprotein (LPAP). LPAP forms a supramolecular complex that consists of not only CD45 molecule but also CD4 and Lck kinase. The function of LPAP has not been defined clearly. In ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…LPAP from Jurkat cells and other lymphoblastoid cell lines is phosphorylated [ 27 , 29 ], but whether this holds true for primary cells is unclear. To address this issue, freshly isolated peripheral blood mononuclear cells (PBMCs) were labeled with Cy3/Cy5, lysed, and LPAP was immunoprecipitated and analyzed by SDS-PAGE or difference gel electrophoresis (2D-DIGE).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…LPAP from Jurkat cells and other lymphoblastoid cell lines is phosphorylated [ 27 , 29 ], but whether this holds true for primary cells is unclear. To address this issue, freshly isolated peripheral blood mononuclear cells (PBMCs) were labeled with Cy3/Cy5, lysed, and LPAP was immunoprecipitated and analyzed by SDS-PAGE or difference gel electrophoresis (2D-DIGE).…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of the first band represents the quantity of the unphosphorylated and pS153 mono-phosphorylated forms. Taking into account our previous results [ 27 ], demonstrating that the level of unphosphorylated LPAP was approximately 15%, we calculated the proportion of the pS153 mono-phosphorylated form to be approximately 40%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Filatov showed that LPAP has at least four sites of phosphorylation and that resting (non-activated) cells express at least six different LPAP proteoforms depending on phospho-state. Additionally, T and B cells differed in the relative abundance of the various phosphoproteoforms, indicating possible differences in their roles [92].…”
Section: Phosphorylationmentioning
confidence: 99%